2018
DOI: 10.1097/md.0000000000009865
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for clinically significant pharmacist interventions at hospital admission

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
16
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 45 publications
7
16
1
8
Order By: Relevance
“…Most of the unintended discrepancies in this study consisted of drug omissions (72%) as similarly reported in the literature [16, 18, 3639]. In such cases, the patient is failing to receive a pre-admission home medication that was deemed necessary by a HCP.…”
Section: Discussionsupporting
confidence: 59%
“…Most of the unintended discrepancies in this study consisted of drug omissions (72%) as similarly reported in the literature [16, 18, 3639]. In such cases, the patient is failing to receive a pre-admission home medication that was deemed necessary by a HCP.…”
Section: Discussionsupporting
confidence: 59%
“…This result is higher than that reported in the literature. 12 This is probably explained by the full-time presence of the two pharmacists in the ward and also because they searched additional clinical, biological and treatment data outside the hospital. All PIs were immediately transmitted orally or by phone call to the prescribers and a response was obtained in 100% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…The French Society of Clinical Pharmacy (SFPC) developed and validated a multidimensional tool for assessing the whole impact of PIs, named CLEO (CLinical, Economic, and Organizational) ( Fig. 1) [17,18]. The CLEO tool includes three independent dimensions to evaluate clinical, economic and organizational impact of PIs to describe the whole impact of PI.…”
Section: Introductionmentioning
confidence: 99%